Economic Impact of Dengue: Multicenter Study across Four Brazilian Regions. - Celina Maria Turchi Martelli; Joao Bosco Siqueira; Mirian Perpetua Palha Dias Parente; Ana Laura de Sene Amancio Zara; Consuelo Silva Oliveira; Cynthia Braga; Fabiano Geraldo Pimenta; Fanny Cortes; Juan Guillermo Lopez; Luciana Ribeiro Bahia; Marcia Costa Ooteman Mendes; Michelle Quarti Machado da Rosa; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Dengue is an increasing public health concern in Brazil. There is a need for an updated evaluation of the economic impact of dengue within the country. We undertook this multicenter study to evaluate the economic burden of dengue in Brazil. METHODS:We estimated the economic burden of dengue in Brazil for the years 2009 to 2013 and for the epidemic season of August 2012- September 2013. We conducted a multicenter cohort study across four endemic regions: Midwest, Goiania; Southeast, Belo Horizonte and Rio de Janeiro; Northeast: Teresina and Recife; and the North, Belem. Ambulatory or hospitalized cases with suspected or laboratory-confirmed dengue treated in both the private and public sectors were recruited. Interviews were scheduled for the convalescent period to ascertain characteristics of the dengue episode, date of first symptoms/signs and recovery, use of medical services, work/school absence, household spending (out-of-pocket expense) and income lost using a questionnaire developed for a previous cost study. We also extracted data from the patients' medical records for hospitalized cases. Overall costs per case and cumulative costs were calculated from the public payer and societal perspectives. National cost estimations took into account cases reported in the official notification system (SINAN) with adjustment for underreporting of cases. We applied a probabilistic sensitivity analysis using Monte Carlo simulations with 90% certainty levels (CL). RESULTS:We screened 2,223 cases, of which 2,035 (91.5%) symptomatic dengue cases were included in our study. The estimated cost for dengue for the epidemic season (2012-2013) in the societal perspective was US$ 468 million (90% CL: 349-590) or US$ 1,212 million (90% CL: 904-1,526) after adjusting for under-reporting. Considering the time series of dengue (2009-2013) the estimated cost of dengue varied from US$ 371 million (2009) to US$ 1,228 million (2013). CONCLUSIONS:The economic burden associated with dengue in Brazil is substantial with large variations in reported cases and consequently costs reflecting the dynamic of dengue transmission.